Denotative and Connotative Meanings in Somethinc’s Promotional Visuals and Their Impact on Parasocial Relationships on X - Regina Clarissa Anindya; Ice Sariyati; R. Myrna Nur Sakinah (Prodi Tadris Bahasa Inggris, 2026)
This study employs a qualitative descriptive approach. The primary data consist of Somethinc’s promotional image posted on November 10, 2025, along with audience responses collected from posts, replies, and discussions on X. The data were analyzed through two stages: semiotic analysis to identify denotative and connotative meanings, and parasocial analysis to interpret emotional reactions from fandom communities. The findings reveal that visual elements such as color, symbols, and textual slogans generate multiple layers of meaning that are interpreted differently across audiences. While the image appears as a strategic marketing design at the denotative level, its connotative meanings are shaped by cultural codes and emotional contexts. For fandom communities with strong parasocial attachment, these meanings are perceived as symbolic threats, triggering collective emotional responses such as criticism, backlash, and boycott. This study demonstrates that visual communication in digital branding is not only semiotic but also deeply influenced by parasocial dynamics.